Network Biology Identifies Novel Regulators of CFTR Trafficking and Membrane Stability - Loureiro, Cláudia Almeida; Santos, João D.; Matos, Ana Margarida; Jordan, Peter; Matos, Paulo; Farinha, Carlos M.; Pinto, Francisco R. (Frontiers in Pharmacology, 2019)
In cystic fibrosis the most common disease-causing mutation is F508del, which causes not only intracellular retention and degradation of CFTR, but also defective channel gating and decreased membrane stability of the small amount that reaches the plasma membrane (PM). Thus, pharmacological correction of mutant CFTR requires targeting of multiple cellular defects in order to achieve clinical benefit. Although small molecule compounds have been identified and commercialized that can correct its folding or gating, an efficient retention of F508del CFTR at the PM has not yet been explored pharmacologically despite being recognized as a crucial factor for improving functional rescue of chloride transport. In ongoing efforts to determine the CFTR interactome at the PM, we used three complementary approaches: targeting proteins binding to tyrosine-phosphorylated CFTR, protein complexes involved in cAMP-mediated CFTR stabilization at the PM, and proteins selectively interacting at the PM with rescued F508del-CFTR but not wt-CFTR. Using co-immunoprecipitation or peptide-pull down strategies, we identified around 400 candidate proteins through sequencing of complex protein mixtures using the nano-LC Triple TOF MS technique. Key candidate proteins were validated for their robust interaction with CFTR-containing protein complexes and for their ability to modulate the amount of CFTR expressed at the cell surface of bronchial epithelial cells. Here we describe how we explored the above-mentioned experimental datasets to build a protein interaction network with the aim to identify novel pharmacological targets to rescue CFTR function in CF patients. We identified and validated novel candidate proteins that were essential components of the network but not detected in previous proteomic analyses.